Morphotypes of the lacustrine ostracod Limnocythere rionegroensis Cusminsky & Whatley from Patagonia, Argentina, shaped by aquatic environments - Ramos, Lorena Yésica (2017)
This study describes and quantifies morphological valve traits of the ostracod Limnocythere rionegroensis from Patagonian steppe lakes and explores their association with lake water characteristics. Surface ornamentation was examined by scanning electron and transmitted light microscopy, and valve size and shape were analyzed using morphometric techniques. Limnocythere rionegroensis shows remarkable variations in surface ornamentation, based on which three morphotypes (MI, MII, and MIII) were identified. Valves of morphotypes MI and MIII are larger, show slight to moderate external reticulation, and a higher shape variability, whereas MII is characterized by a very conspicuous reticulation, lower shape variability, and smaller valves. Outline analysis yielded a great shape disparity related to the dorsal margin slope. MI was found in sexual populations from euhaline to mesohaline ephemeral lake; MII occurs in parthenogenetic populations from mesohaline to oligohaline permanent or ephemeral lakes; and MIII, from both sexual and asexual populations, inhabits a broad range of environmental conditions in terms of salinity and stability. Limnocythere rionegroensis intraspecific variations may be caused by environmental parameters and genetic factors associated to reproductive strategies. These results contribute to the knowledge of extant L. rionegroensis morphological variability and provide additional clues to improve the environmental interpretation of fossil assemblages.